Pengaruh Literasi Keuangan, Pemanfaatan Teknologi Informasi Dan Penggunaan Informasi Akuntansi Terhadap Kinerja UMKM Di Kecamatan Teras Kabupaten Boyolali - Nafisa Amalia Afifah; Eko Triyanto (CV. ALIM'SPUBLISHING, 2023)
The purpose of this study was to know the effect of financial literacy, use of information technology, and use of accounting information on the performance of MSMEs. This research was conducted on MSMEs in Teras District, Boyolali Regency. This type of research is quantitative. Data collection techniques used literature studies, questionnaires and observation. The population of this study is MSMEs in Teras District, Boyolali Regency are 145 MSMEs engaged in the food and beverage sector and are already used social media to sell their wares. The sampling technique used slovin with a sample of 60 respondents. Data analysis techniques used multiple linear regression, t test, F test and the coefficient of determination. The results of the study show that financial literacy has an effect on the performance of MSMEs, the use of information technology has an effect on the performance of MSMEs and the use of Accounting Information Systems has an effect on the performance of MSMEs. Financial literacy, use of information technology and accounting information systems affect the performance of MSMEs simultaneously.